The uncertainty of treatment: Women's use of HIV treatment as prevention in Malawi. (June 2016) - Zhou, Amy
Abstract: In countries throughout sub-Saharan Africa, antiretroviral therapy is seen as the solution to not only treat existing patients, but also to prevent the future spread of HIV. New policies for the prevention of mother-to-child transmission place women on lifelong treatment as soon as they are tested HIV positive. This article looks at how women understand this prescription for lifelong treatment. Drawing on interviews with HIV-positive women in Lilongwe, Malawi (N = 65) during July–September 2014, I examine the process of making treatment decisions, and why – despite increased access – women refuse or stop treatment. Using treatment for preventative purposes transforms the experience of HIV from an acute to a chronic condition where both the symptoms of disease and the efficacy of treatment are unclear. Women look for evidence of the cost and benefit of treatment through their personal experiences with illness and drug-taking. For some women, the benefits were clearer: they interpreted past illnesses as signs of HIV infection, and felt healthier and more economically productive afterwards. For others, taking treatment sometimes led to marital problems, and side effects made them feel worse and disrupted their ability to work. While women understand the health benefits of antiretroviral therapy, taking treatment does not always make sense in their present circumstances when there are costly physical and economic repercussions. This study builds on existing sociological research on medical decision-making by situating decisions in a broader political economy of changing HIV policies, economic conditions, and everyday uncertainty. Highlights: Examines decision-making process for HIV treatment as prevention. Describes how HIV positive Malawi women understand Option B+. Unique interview sample that covers a range of treatment experiences. Situates treatment decisions in a political economy of HIV policy and economic constraints.